2006
DOI: 10.1164/rccm.200503-509oc
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tobacco Smoke Suppresses Nuclear Factor-κB Signaling to Increase Apoptosis in Infant Monkey Lungs

Abstract: Rationale: Exposure to environmental tobacco smoke in early life has adverse effects on lung development. Apoptosis plays an essential role in development; however, the molecular mechanisms of pulmonary apoptosis induced by environmental tobacco smoke is unknown. Objectives: To investigate the mechanistic role of nuclear factor (NF)-B, a critical cell survival pathway, in the developing lungs exposed to environmental tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 70 publications
1
22
1
Order By: Relevance
“…Exposure to SHS during the perinatal period suppresses NF-k B activity in the neonatal nonhuman primate and exposure to mainstream cigarette smoke inhibits NF-k B in human monocytes. 32,33 Conversely, exposure to cigarette smoke increases NF-k B activity in vitro. 34 Th ese observations suggest that cigarette smoke-mediated activation of NF-k B is tissue specifi c. Interestingly, despite an overall increase in endothelial NF-k B expression in passive smokers, we observed that prolonged exposure to SHS ( .…”
Section: Figure 1 -Expression Of Markers Of Endothelial Reactivity Imentioning
confidence: 99%
“…Exposure to SHS during the perinatal period suppresses NF-k B activity in the neonatal nonhuman primate and exposure to mainstream cigarette smoke inhibits NF-k B in human monocytes. 32,33 Conversely, exposure to cigarette smoke increases NF-k B activity in vitro. 34 Th ese observations suggest that cigarette smoke-mediated activation of NF-k B is tissue specifi c. Interestingly, despite an overall increase in endothelial NF-k B expression in passive smokers, we observed that prolonged exposure to SHS ( .…”
Section: Figure 1 -Expression Of Markers Of Endothelial Reactivity Imentioning
confidence: 99%
“…Both epithelial cells and endothelial cells die, and their apoptosis has been demonstrated in human and animal lungs (34,62,(91)(92)(93). The loss of alveolar capillary endothelial cells and of small capillaries (94) de facto makes emphysema also a vascular disease (95)(96)(97)(98)(99).…”
Section: No Vegf No Growth -Only Deathmentioning
confidence: 99%
“…NF-κB is the major transcription factor that controls the apoptotic process and regulates the transcription of a broad range of gene products (Zhong et al 2006), including those activated in response to various oxidative stresses, being crucially involved in inflammation, apoptosis, and proliferation in lung tissue (Dagher et al 2006;Valença et al 2006). NF-κB has also been shown to be stimulated in response to diverse pathogenic particles (Churg et al 2005;Dagher et al 2007;Park and Christman 2006;Pourazar et al 2005;Takizawa et al 1999;Takizawa 2004;Valença et al 2006;Zhong et al 2006).…”
Section: Activation Of the Mapk Cascades And Transcription Factorsmentioning
confidence: 99%